Crop residue recycling for economic and environmental sustainability: The case of India - Devi Saroj; Gupta Charu; Jat Shankar Lal; Parmar M.S. (Open Agriculture, 2017)
India is one of the key producers of food grain, oilseed, sugarcane and other agricultural products. Agricultural crops generate considerable amounts of leftover residues, with increases in food production crop residues also increasing. These leftover residues exhibit not only resource loss but also a missed opportunity to improve a farmer’s income. The use of crop residues in various fields are being explored by researchers across the world in areas such as textile composite non-woven making processes, power generation, biogas production, animal feed, compost and manures, etc. The increasing trend in addition of bio-energy cogeneration plants, increasing demand for animal feedstock and increasing trend for organic agriculture indicates a competitive opportunity forcrop residue in Agriculture. It is to be noted that the use of this left over residue isoften not mutually exclusive which makes measurement of its economic value more difficult.For example, straw can be used as animal bedding and thereafter as a crop fertilizer. In view of this, the main aim of this paper envisaged to know about how much crop residue is left unutilized and how best they can be utilized for alternative purposes for environmental stewardship and sustainability. In this context, an attempt has been made to estimate the total crop residue across the states and its economic value though data available from various government sources and a SWOT analysis performed for possible alternative uses of residue in India. This paper also discusses the successful case studies of India and global level of use of crop residues in economic activities. Over all 516 Mtonnes of crop residue was produced in 2014-15 in India among which cereals were the largest producer of crop residue followed by sugarcane. The energy potential from paddy rice straw crop residue was estimated as 486,955 megawatt for 2014-15 and similarly for coarse cereals it was 226,200megawatt.